Low temperature solvolthermally synthesized nitrogen-fluorine doped TiO 2 for methyl orange photodegradation - Tanagorn Kwamman (2018)
A low temperature solvothermal method was employed to synthesize nitrogen-fluorine doped TiO 2 materials (N/F -TiO 2 ) at various mole ratio of Ti:F; 10:1, 10:0.3 and 10:0.1, for photocatalytic applications. Doping fluorine and nitrogen in the TiO 2 structure extend the spectra response of the materials toward a visible region resulting in the high efficiency to oxidize methyl orange (MO) under UV-Vis irradiation. The microstructure and photocatalytic activity of the materials appeared to depend on titanium precursors, titanium isopropoxide (TTIP) or tetrabutyl orthotitanate (TBOT), and the concentration of dopant (NH4F). The highest MO decolorization efficiency under UV-Vis irradiation for 30 minutes is about 86 % by using N-F-TiO 2 (TTIP precursor) with Ti: F of 10: 3 as catalyst. The decolorization efficiencies of MO over N-F-TiO 2 materials (TTIP precursor) are twice higher than that of the undoped catalyst. © (2012) Trans Tech Publications.